Inclusive Education in the Russian Federation Scoping International and Local Relevance - Makoelle, Tsediso Michael; Kozlova, Maria; Iarskaia-Smirnova, Elena (Springer Nature Switzerland : Imprint: Springer, 2024)
XXII, 310 p. 36 illus., 14 illus. in color.